2021
DOI: 10.1016/j.csbj.2021.08.054
|View full text |Cite
|
Sign up to set email alerts
|

CDPKs: The critical decoders of calcium signal at various stages of malaria parasite development

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Due of their absence from their mammalian hosts, they are regarded as potential druggable targets. In Plasmodium spp., CDPKs play essential roles at various critical physiological stages during parasite development, including merozoite invasion and asexual intraerythrocytic development in humans and sexual/pre-erythrocytic development in Anopheles mosquitoes [ 61 ]. Currently, fourteen CDPKs have been identified that contribute to several functions in the biological processes of T. gondii , such as gliding motility, cell invasion, and egress [ 62 ].…”
Section: Intraparasitic Egress Signalingmentioning
confidence: 99%
“…Due of their absence from their mammalian hosts, they are regarded as potential druggable targets. In Plasmodium spp., CDPKs play essential roles at various critical physiological stages during parasite development, including merozoite invasion and asexual intraerythrocytic development in humans and sexual/pre-erythrocytic development in Anopheles mosquitoes [ 61 ]. Currently, fourteen CDPKs have been identified that contribute to several functions in the biological processes of T. gondii , such as gliding motility, cell invasion, and egress [ 62 ].…”
Section: Intraparasitic Egress Signalingmentioning
confidence: 99%
“…PKAc1 suppresses egress in T. gondii but is instead required for invasion by P. falciparum 10,12,68−71 . The CDPK family of proteins are also required for P. falciparum and T. gondii egress and invasion, although the direct orthologs (de ned by reciprocal blast) do not always have the same function between species (Reviewed in 72,73 ). PLPs are involved in host cell permeabilization and egress in T. gondii, Plasmodium spp.…”
Section: Identi Cation Of Putative Egress Motility and Invasion Genes...mentioning
confidence: 99%